Postoperative Opioid Consumption and Its Relationship to Cognitive Function in Elderly Hip Fracture Patients - Sieber, Frederick E. (2011)
OBJECTIVES: To determine the relationship between opioid consumption and cognitive impairment following hip fracture repair. DESIGN: Prospective study of consecutive patients. SETTING: Johns Hopkins Bayview Medical Center; Baltimore, Maryland. PARTICIPANTS: Two hundred thirty-six patients ≥65 years old undergoing hip fracture repair. MEASUREMENTS: Elderly patients without preoperative delirium who underwent hip fracture repair between April 2005 and July 2009 were followed for pain, opioid consumption, and postoperative delirium. Patients were tested for delirium with the confusion assessment method preoperatively and mid-morning on postoperative day 2. Pain was assessed by the nursing staff with a numeric 0–10 verbal scale. Opioid analgesia was provided in response to pain at rest to achieve scores of ≤3. Opioid consumption was analyzed with respect to the occurrence of incident postoperative delirium, presence of dementia, and other demographic variables. RESULTS: Of the 236 patients, 66 (28%) had dementia with 213 (90%) receiving opioids postoperatively; including 55 (83%) demented patients and 158 (93%) non-demented patients. There was no association between the use of any postoperative opioid and incident delirium (P=0.615) in both demented (p=0.333) and non-demented patients (P=0.398). Dementia, but not postoperative delirium, was associated with less opioid use (P<0.001 for dementia; P=0.120 for delirium; P=0.038, for their interaction; Wald χ(2) =142.8 with 7 d.o.f.). Furthermore, opioid dose (P≥0.591) on postoperative days 1 and 2 was not predictive of incident delirium. Dementia (P<0.001) and intensive care unit admission (P=0.006), not opioid consumption, were the most important predictors of incident postoperative delirium. CONCLUSION: Concern for postoperative delirium should not prevent the use of opioid analgesic therapy sufficient to achieve a generally accepted level of comfort in patients with or without preexisting cognitive impairment.